Characteristics Analysis of Glamping Visitors in The Covid-19 Pandemic (Case Study on Glamping Lakeside Rancabali) - Baskoro Harwindito; Asmawih; Armand; Hady Chandra Kurniawan4; Michelle Angel (International Journal of Travel, Hospitality and Events, 2024)
Purpose: The purpose of this study was to determine the analysis of the characteristics of glamping visitors during the covid-19 pandemic at Glamping Lakeside Rancabali. Research metods: In obtaining the desired research results, this study used descriptive research methods with a quantitative approach, and purposive sampling through questionnaires. Result and discussion: The results of this study indicate that in general the analysis of the characteristics of glamping visitors is seen from positive environmental, personal, and social factors on a trip or vacation to Glamping Lakeside Rancabali. Implication: In this study, it can be concluded that the gender of the respondents, both male and female, is 42 (male) and 33 (female), the age characteristics of Glamping Lakeside Rancabali visitors are dominated by young adults, namely 21-30 years, from the province and domiciled in DKI Jakarta, the most recent education attained by the most respondents is the respondent with a high school education level, the income or income of the most respondents is the respondent with an income of IDR 2,500,000 – IDR 3,500,000. The results of the CHAID analysis obtained by researchers are the dependent variable used in this study, namely public transportation, while for the independent variables (free) used are 10 other indicators. The conclusion obtained is that the chi-square test is h0 rejected, which means that the dependent and independent variables have a relationship.   Keywords: Glamorous Camping, Guest Characteristics, Covid-19 Pandemic